Alternative lengthening of telomeres, ATRX loss and H3‐K27M mutations in histologically defined pilocytic astrocytoma with anaplasia. (17th October 2018) - Rodriguez, Fausto J.; Brosnan‐Cashman, Jacqueline A.; Allen, Sariah J.; Vizcaino, M. Adelita; Giannini, Caterina; Camelo‐Piragua, Sandra; Webb, Milad; Matsushita, Marcus; Wadhwani, Nitin; Tabbarah, Abeer; Hamideh, Dima; Jiang, Liqun; et al.
Abstract: Anaplasia may be identified in a subset of tumors with a presumed pilocytic astrocytoma (PA) component or piloid features, which may be associated with aggressive behavior, but the biologic basis of this change remains unclear. Fifty‐seven resections from 36 patients (23 M, 13 F, mean age 32 years, range 3–75) were included. A clinical diagnosis of NF1 was present in 8 (22%). Alternative lengthening of telomeres (ALT) was assessed by telomere‐specific FISH and/or CISH. A combination of immunohistochemistry, DNA sequencing and FISH were used to study BRAF, ATRX, CDKN2A /p16, mutant IDH1 p.R132H and H3‐K27M proteins. ALT was present in 25 (69%) cases and ATRX loss in 20 (57%), mostly in the expected association of ALT+/ATRX‐ (20/24, 83%) or ALT‐/ATRX+ (11/11, 100%). BRAF duplication was present in 8 (of 26) (31%). H3‐K27M was present in 5 of 32 (16%) cases, all with concurrent ATRX loss and ALT. ALT was also present in 9 (of 11) cases in the benign PA precursor, 7 of which also had ATRX loss in both the precursor and the anaplastic tumor. In a single pediatric case, ALT and ATRX loss developed in the anaplastic component only, and in another adult case, ALT was present in the PA‐A component only, but ATRX was not tested. Features associated with worse prognosis included subtotal resection, adult vs. pediatric, presence of a PA precursor preceding a diagnosis of anaplasia, necrosis, presence of ALT and ATRX expression loss. ALT and ATRX loss, as well as alterations involving the MAPK pathway, are frequent in PA with anaplasia at the time of development of anaplasia or in their precursors. Additionally, a small subset of PA with anaplasia have H3‐K27M mutations. These findings further support the concept that PA with anaplasia is a neoplasm with heterogeneous genetic features and alterations typical of both PA and diffuse gliomas.